Les agglomérations de Sarrebourg/Pons Saravi (Moselle) et de Saverne/Tabernis-Tres Tabernae (Bas-Rhin) : deux destins de part et d’autre des Vosges durant l’Antiquité tardive - Nicolas Meyer (Gallia)
This paper provides an overview of the research conducted in two similar Roman towns, Pons Saravi (Sarrebourg, Moselle) and Tabernis‑Tres Tabernae (Saverne, Bas-Rhin), both located on the imperial west/east road connecting the provinces of Gallia and Germania and on both sides of the main pass of the North Vosges. It favors the later occupation in the middle of the 3rd c., both towns have comparable sizes between 12 and 14 ha and perform activities which go much beyond their road function. In the middle of the 3rd c. AD, the situation is quite different: a fortification is built around the town of Tabernis‑Tres Tabernae. The town becomes the key point for the defence of the imperial road and does not loose much size. Pons Saravi is protected at best by a burgus and is reduced by the two thirds of its original size. Nevertheless the town keeps a certain dynamism with new public buildings around a long-lasting spring of the town, which has been highlighted by the rescue archaeology campaigns, the presence of a Christian community and a mithraeum.